Renal manifestations in children with neurofibromatosis type 1 - Celik, Binnaz; Aksoy, Ozlem Yuksel; Bastug, Funda; Poyrazoglu, Hatice Gamze (Springer, 2021)
Neurofibromatosis type 1 (NF1) is an autosomal-dominant neurocutaneous syndrome affecting various parts of the body, including the renovascular and urinary systems. We evaluated the renovascular, urinary, glomerular, and tubular functions of children with NFL We compared blood pressures, urinary findings, and renal glomerular and tubular functions in children with NF1 with those of a healthy age- and gender-matched control group. We evaluated 46 NF1 patients and 33 healthy controls. The mean ages of the NF1 group (female/male: 20/26) and the control group (female/male: 15/18) were 10.1 +/- 4.6 and 10.6 +/- 4.3 years respectively. Six NF1 patients were hypertensive. The mean blood pressures of the NF1 group were significantly higher than those of the control group. Renal artery stenosis was detected in one NF1 patient. Urinary tract anomalies were evident in 21.7% of NF1 but only 9% of control subjects. The mean estimated glomerular filtration rate (eGFR) of the NF1 group was significantly lower than that of the control group. Six NF1 patients evidenced eGFRs < 90 mL/min. In the NF1 group, tubular phosphorus reabsorption was significantly lower and uric acid excretion significantly higher than in the control group. Conclusion: Hypertension, urinary tract anomalies, and impaired renal function were more common in NF1 patients than healthy controls. Regular blood pressure measurements and evaluation of urinary tract and kidney function are essential for NF1 patients.
Keywords: Children; eGFR; Neurofibromatosis type 1; Renal manifestations